Information system development methodology enabling business process reuse - Čiukšys, Donatas (Lietuvos matematikos rinkinys, 2004)
The paper outlines IS development methodology based on reuse ideas developed in knowledge engineering and ontology-based system engineering fields. This methodology enables business process reuse. Paper focuses on location of business process in business domain and assignment of business process roles to business domain entities.